Modulation of subventricular zone oligodendrogenesis: a role for hemopressin? - Xapelli, Sara; Agasse, Fabienne; Grade, Sofia; Bernardino, Liliana; Ribeiro, Filipa; Schitine, Clarissa S.; Heimann, Andrea; Ferro, Emer S.; Sebastião, Ana M.; de Melo Reis, Ricardo A.; Malva, João O. (Frontiers in Cellular Neuroscience, 2014)
Neural stem cells (NSCs) from the subventricular zone (SVZ) have been indicated as a source of new oligodendrocytes to use in regenerative medicine for myelin pathologies. Indeed, NSCs are multipotent cells that can self-renew and differentiate into all neural cell types of the central nervous system. In normal conditions, SVZ cells are poorly oligodendrogenic, nevertheless their oligodendrogenic potential is boosted following demyelination. Importantly, progressive restriction into the oligodendrocyte fate is specified by extrinsic and intrinsic factors, endocannabinoids being one of these factors. Although a role for endocannabinoids in oligodendrogenesis has already been foreseen, selective agonists and antagonists of cannabinoids receptors produce severe adverse side effects. Herein, we show that hemopressin (Hp), a modulator of CB1 receptors, increased oligodendroglial differentiation in SVZ neural stem/progenitor cell cultures derived from neonatal mice. The original results presented in this work suggest that Hp and derivates may be of potential interest for the development of future strategies to treat demyelinating diseases.